Strategi Pemasaran Dalam Meningkatkan Daya Saing Di Era Pemasaran Modern (Studi Pada Sumber Agung Fashion Kabupaten Tulungagung) - Yani Maila Santi; Indah Respati Kusumasari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research highlights the marketing strategies used by Sumber Agung Fashion in maintaining and improving its competitiveness in the modern marketing era. The purpose of this study is to find out how the marketing strategy used by Sumber Agung Fashion and to find out what are the strengths, weaknesses, opportunities, or threats to Sumber Agung Fashion Tulungagung Regency. The research method used in this study is qualitative descriptive using SWOT analysis techniques. Based on the results of the SWOT analysis that has been conducted, Sumber Agung Fashion has a strength score of 2.36, weakness of 0.74, chance of 1.58 and threat of 1.18, thus showing that Sumber Agung Fashion is in the position of Quadrant I which supports aggressive strategies. In addition, in the SWOT matrix, it can be seen that the right strategy used by Sumber Agung Fashion Tulungagung Regency in order to compete in this modern marketing era is to use the SO strategy, including by maintaining product quality and service to Sumber Agung Fashion consumers, maintaining good relations with consumers, and expanding the target market to other cities and using technology (e-commerce) as a product marketing.